The politics of language and football coaching in Zimbabwe: Implications on the development of the sport (Namibian Journal of Linguistics, Literature and Communication Studies, 2023)
This article examines how the language policy of the Zimbabwe Football Association (ZIFA) influences the selection of the language used in the delivery of the Confederation of African Football (CAF) coaching courses and how this choice impacts football development in Zimbabwe. Linguistic imperialism (Phillipson, 1992) was adopted as the theoretical framework for this study. Using document analysis, the study investigates how ZIFA’s language policy accommodates or excludes people of different languages in football activities. The language policies of FIFA, CAF, and those regional football associations are also analysed to appreciate how they compare with the language policy of ZIFA. Six principles drawn from Phillipson’s (1992) theory of linguistic imperialism were used as tools of analysis in this research. Findings from this study were presented following themes that emanated from language provisions as presented in documents selected as sources of data for the study. The study revealed that the hegemony of European languages has been perpetuated in football matters, with English maintaining traction in ZIFA’s statutes, as the bona fide language of football. Consequently, the participation of some speakers of indigenous languages in football activities such as coaching courses has been curtailed.
Keywords: language politics; language policy; language choices; football development